Anti-Cancer Activity of Nitrones and Observations on Mechanism of Action - A. Floyd, Robert; K. Chandru, Hema; He, Ting; Towner, Rheal (Anti-Cancer Agents in Medicinal Chemistry, 2011)
The nitrone compound PBN, α-phenyl-tert-butylnitrone, and closely related nitrones have anti-cancer activity in several experimental cancer models. The three experimental models most extensively studied include A) the rat choline deficiency liver cancer model, B) the rat C6 glioma model and C) the mouse APCMin/+ colon cancer model. The two PBN-nitrones mostly studied are PBN and a PBN derivative 2,4-disulfophenyl-tert-butylnitrone, referred as OKN-007. OKN-007 is a proprietary compound that has had extensive commercial development (designated as NXY-059) for another indication, acute ischemic stroke, and after extensive clinical studies was shown to lack efficacy for this indication but was shown to be very safe for human use. This compound administered orally in the rat glioma model has potent activity in treating fully formed gliomas. In this report observations made on the PBN-nitrones in experimental cancer models will be summarized. In addition the experimental results will be discussed in the general framework of the properties of the compounds with a view to try to understand the mechanistic basis of how the PBN-nitrones act as anti-cancer agents. Possible mechanisms related to the suppression of NO production, S-nitrosylation of critical proteins and inhibition of NF-κB activation are discussed.
Keywords: colon cancer